KEDUDUKAN HUKUM BITCOIN SEBAGAI MATA UANG VIRTUAL DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2011 TENTANG MATA UANG - Clara .; Siti Nurbaiti (Jurnal Hukum Adigama, 2018)
Nowadays people rely on many things in order to do daily activity. As time goes by, global economy has changed and has had significant growth. The form of money has also changed, from only being available in the physical form, such as coins and banknotes, now we have the digital form of money, otherwise known as virtual currency. This paper discusses about the legal status of Bitcoin as virtual currency in Indonesia according to Law Number 7 of 2011 regarding Currency Law. The author examines the problem by using normative legal research methods with descriptive approach. The data was collected from secondary and primary data and is used as supportive research data. The collected data is analysed using qualitative method. The result of this research is the legal status of Bitcoin as virtual currency in Indonesia according to Law Number 7 of 2011 regarding Currency Law has not been regulated yet. Therefore, the government of Indonesia needs to make a specific regulation to regulate Bitcoin in Indonesia.